INTERPRETASI DATA SEISMIK REFLEKSI : PICKING HORIZON DAN PICKING FAULT - Wibowo, Barrend Wellyadi; Hutagalung, Soly Deo Gloria (Journal of Renewable Engineering, 2024)
Seismic method practicum has been carried out with the title "Interpretation of reflection seismic data: picking horizon and picking fault". The seismic method is a geophysical method that is often used in imaging the subsurface conditions of the earth. The purpose of this practicum is to find out how to do picking horizon and picking fault. Picking horizon and picking faults are done with petrel software. Picking Horizon is a method that is carried out by making a horizon line on a continuous layer on a seismic cross section. For picking horizon, petrel software is used. From these data it is known that there are 3 horizons (layers). Fault picking is carried out simultaneously with seismic horizon picking. Fault picking is carried out starting from a clear shift in the horizon and continuing to the vertical shift zone. For picking faults, petrel software is used. From these data it is known that there are 4 faults (faults).